Decision-Making Framework for Implementing Blockchain in Building Operations and Maintenance (O&M) - Kifokeris, Dimosthenis; Tezel, Algan; Moon, Sungkon (Computing in Civil Engineering 2023: Visualization, Information Modeling, and Simulation - Selected Papers from the ASCE International Conference on Computing in Civil Engineering 2023, 2024)
Blockchain is a distributed ledger technology that verifies and records transactions simultaneously across a computer network, offering data dependability, traceability, and immutability. It has gained attention in the architecture, engineering, construction, and operations (AECO) industry. However, to justify its deployment costs, it is essential to identify where blockchain can generate the most value. This study proposes that the operations and maintenance (O&M) phase of a building's life cycle, which has a significant environmental, social, and economic impact, can yield a higher return for blockchain. A literature review was conducted to investigate the implementation of blockchain in AECO, revealing a need for more attention to O&M. Inspired by the insights from the review and existing blockchain deployment frameworks, a high-level decision-making framework for blockchain adoption in O&M was developed. The paper also discusses various opportunities, challenges, and future research questions for a successful implementation of blockchain in buildings' O&M.
Keywords: Architecture engineering; Block-chain; Building maintenance; Building operations; Decision-making frameworks; Deployment costs; Engineering constructions; Engineering operation; In-buildings; Operations and maintenance